Dispersion‐Engineered Super‐Gain Parametric Amplification in Nanoscale Optical Cavities - Özüm Emre Aşırım (Advanced Photonics Research, 2024)
The gain factor of the optical parametric amplification (OPA) process is known to be negligible in the small scale due to low‐interaction‐medium length. Hence, in the nanoscale, OPA is deemed as infeasible. Therefore, in small‐scale‐integrated optical devices, stimulated‐emission‐based amplifiers (lasers) are employed instead of OPAs. In contrast, the major advantage of OPAs over lasers is that unlike lasers which only provide amplification over a narrow spectral band, OPAs provide high‐gain amplification over a very large, user‐controlled spectral band. In this article, it is shown that OPA can yield wideband high‐gain amplification over a nanoscale beam propagation distance through dispersion engineering. This is achieved by a proper tuning of the pump (source) wave frequency, which can maximize the effective medium nonlinearity by a few orders of magnitude, while concurrently maximizing the intracavity energy density, thereby compensating for the small co‐propagation distance for the input (signal) and pump beams. In this study, it is shown that an input wave can be amplified by a factor 108 in a nanoscale cavity via precise dispersion engineering. Both empirical and computational formulations are used for the investigation, which display a reasonable agreement.